The Effect of Variety , Gibberellic Acid And NPK Fertilizer and their Interactions On Absorption and Transport Rates of Some Macronutrient Elements in Chamomile plant - Al-Saedi, A.J.H.; Al-Rubaiee, F.A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This experiment was carried out in the field of botanical garden which belongs to Biologi Department , College of Education (Ibn Al-Haitham), University of Baghdad during the growing season 2009-2010.The experiment was designed to study the effect 5 concentrations of Gibberellic acid(GA3)( 25,50,75,100and125mg.L-1) and 2 levels of NPK (17:17:17) fertilizer (200 and 400 Kg.ha-1) and their interaction on the rates of absorption and transport of some macronutrient elements in two varieties of chamomile plant ( Local variety , Matricaria chamomilla L. and German variety , Matricaria recutitia L.) . Randomized Complete Block Design (RCBD) was used with 3 replicates for each treatment .Control plants were grown in unfertilized soils and not sprayed with gibberellic acid . Results showed a significant increase in the absorption and transport rates of N,P,K,Ca and Mg with increased GA3 concentration and NPK levels in comparision with the control plants The highest rates of absorption and transport rates were obtained by using GA3 at 75 mg.L-1and NPK at 400 Kg.ha-1. The local variety gave highest rates of absorption and transport .This result pointed to the genetic variations between the two varieties in their response to the studied factores